Experience of pharmacist-led antimicrobial stewardship ward rounds in a regional hospital. Issue 2 (28th February 2020) - Bond, Stuart; Ashton, Kathryn; Lee-Milner, Jade; Mustapha, Damilola; Hinchliffe, Rachael; Walker, Nicola
Abstract : Background: Antimicrobial stewardship ward rounds and phone advice are fundamental to improvement of infection treatment and prevention in hospitals. In response to a local and national shortage of consultant medical microbiologists, a pharmacist-led antimicrobial stewardship service was established. Methods: Antimicrobial stewardship interventions in a large regional hospital were analysed from 8 January 2018 to 14 March 2019. Collaborative ward rounds were conducted with infection prevention and control nurses, and microbiology staff when available. Ad hoc ward rounds and phone interventions (via a dedicated "antibiotic advice hotline") were also conducted, with most referrals coming from junior doctors and ward pharmacists. The commonest clinical areas visited were elderly care, respiratory and general surgery. Results: 1507 antimicrobials were reviewed from 1006 interventions (16 per week). Antimicrobials most reviewed were piperacillin/tazobactam (n=152; 10%), metronidazole (n=152), co-amoxiclav (n=140; 9%), teicoplanin (n=137, 9%) and gentamicin (n=116; 8%). The commonest organisms were Escherichia coli (n=115), Staphylococcus aureus (n=95) and Clostridium difficile (n=52). The most common recommendations were intravenous to oral switch (n=185; 18%), continue (n=175; 17%), escalate (n=136; 14%) and review dose (n=97; 10%). Antimicrobials were optimised for discharge in 270 cases, through oral switch, home intravenous antimicrobial referral or cessation. Conclusion: The results demonstrate the value of novel antimicrobial stewardship approaches that are required in today's NHS given shifts in staff availability and recognising advanced clinical practice among non-medical staff. Future planned interventions will focus on improving the home intravenous antimicrobial referral and review process.